The Emperor's New Drugs : Exploding the Antidepressant Myth. - Kirsch, Irving (Perseus Books Group, 2010)
Do antidepressants work? Of courseeveryone knows it. Like his colleagues, Irving Kirsch, a researcher and clinical psychologist, for years referred patients to psychiatrists to have their depression treated with drugs before deciding to investigate for himself just how effective the drugs actually were. Over the course of the past fifteen years, however, Kirsch's researcha thorough analysis of decades of Food and Drug Administration datahas demonstrated that what everyone knew about antidepressants was wrong. Instead of treating depression with drugs, we've been treating it with suggestion.